2008
DOI: 10.1590/s0100-06832008000300016
|View full text |Cite
|
Sign up to set email alerts
|

Organic material decomposition and nutrient dynamics in a mulch system enriched with leguminous trees in the Amazon

Abstract: SUMMARYThe new techniques proposed for agriculture in the Amazon region include rotational fallow systems enriched with leguminous trees and the replacement of biomass burning by mulching. Decomposition and nutrient release from mulch were studied using fine-mesh litterbags with five different leguminous species and the natural fallow vegetation as control. Samples from each treatment were analyzed for total C, N, P, K, Ca, Mg, lignin, cellulose content and soluble polyphenol at different sampling times over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 40 publications
(54 reference statements)
3
23
0
Order By: Relevance
“…This result shows how easily this element is released during the decomposition process. Rapid release of K from plant tissues during the decomposition process is well known (Giacomini et al, 2003;Cattanio et al, 2008;Teixeira et al, 2011). Among the micronutrients, in general, Mn, Zn, and Fe had the highest average t 1/2 , suggesting lower release rates than B and Cu.…”
Section: Decomposition and Nutrient Release Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result shows how easily this element is released during the decomposition process. Rapid release of K from plant tissues during the decomposition process is well known (Giacomini et al, 2003;Cattanio et al, 2008;Teixeira et al, 2011). Among the micronutrients, in general, Mn, Zn, and Fe had the highest average t 1/2 , suggesting lower release rates than B and Cu.…”
Section: Decomposition and Nutrient Release Dynamicsmentioning
confidence: 99%
“…This is because K is not a structural component of any plant compound (Lupwayi et al, 2006;Gama-Rodrigues et al, 2007) and most of this element in plant tissue (up to 70 %) is in a water soluble form (Giacomini et al, 2003). The mineralization of K depends on the concentrations of C and phenolic compounds during the incubation period (Cattanio et al, 2008). Considering the storage potential of K (Table 2) and the average t 1/2 observed for this element (Figure 5), in only six days, the K content released by the species would be the following: GRAS (154 kg ha ).…”
Section: Decomposition and Nutrient Release Dynamicsmentioning
confidence: 99%
“…Blair et al (1990) found in litterbags containing mixed residues that there were significantly greater initial releases of N and lower subsequent N immobilization than predicted, and they suggest that it resulted from differences in the decomposer community originated from the mixtures of varied litter resource quality. In the same way, Handayanto et al (1997), Kuo andSainju (1998), Zimmer (2002) and Cattanio et al (2008) showed that soil N-mineralization rate of prunings could be manipulated by mixing different quality materials. Different organic materials decompose at contrasting rates because they are decomposed differentially by catabolic enzymes produced by saprophytic organisms (Linkins et al 1984).…”
mentioning
confidence: 93%
“…If burning is to be abandoned, then the synchronization of nutrient release from organic material and nutrient uptake by plants (Addiscott et al 1991, Myers et al 1994, accompanying the competition between plant and microorganisms for nutrients (Cattanio et al 2008), will be the core problem in applied tropical soil biology research. Yield losses in field trials of the SHIFT project have shown that yield losses in mulch practices are evident as compared to burned treatments (Kato et al 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation